REPRESENTASI KEARIFAN LOKAL DALAM NOVEL LA MULI DAN IMPLIKASINYA SEBAGAI PENGUAT KARAKTER MANDIRI - Alim Susilo; Mukti Widayati; Nurnaningsih Nurnaningsih (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study aims to describe the local wisdom presented in the novel La Muli by Nunuk Y. Kusmiana and to explore its implications for reinforcing independent character education.This study uses a descriptive qualitative method with literature study and content analysis. This research is based on the approach of literary sociology. The research data consisted of phrases, sentences, and words in the novel La Muli related to local wisdom. The data sources are in the form of the novel La Muli, by Nunuk Y. Kusmiana, scientific journal articles, and learning tools. Data collection through literature study techniques, record techniques, and document analysis. Sampling was carried out by purposive sampling. The validity of the data is checked through triangulation of data sources and techniques. The data was analyzed using content analysis. The results of the study show that the novel La Muli represents various forms of local wisdom of the Buton people through three categories, namely 1) human-human relations (social relations) shown through respect for parents and social responsibility, 2) human relations with nature and time (ecological relations) are shown from harmony with nature fostering time discipline, sense of responsibility, and resilient attitudes, 3) Human relationships with themselves (spiritual relationships) and 4) Man's relationship with God (theological relationship) are represented through the values of honesty and self-integrity. These values are reflected in the behavior of the main character, La Muli, who is described as an independent, responsible, and integrity person in the midst of the limitations, social and economic challenges he faces. The picture provides important lessons about courage, resilience, and independence. The representation of local wisdom in this novel has strong implications for strengthening independent character education. Local values instilled through stories help students form characters who are courageous, disciplined, and independent of others, in line with the principles of character education. For this reason, the implications of this finding can be used as a basis for the development of literary learning and character education, by integrating local wisdom as a reinforcement of independent character education in the younger generation.